Origin of the optical anisotropy and the electronic structure of Ru-based double perovskite oxides: DFT and XPS studies. Issue 69 (8th September 2017) - Sakhya, Anup Pradhan; Rai, D. P.; Sheikh, Md. Sariful; Mukherjee, Manabendra; Dutta, Alo; Sinha, T. P.
Abstract : Sm2 LiRuO6 has a relatively large birefringence compared to Nd2 LiRuO6 and Pr2 LiRuO6, which is important for mid-infrared nonlinear applications. Abstract : Experimental and theoretical studies of the electronic structure of Pr2 LiRuO6 (PLR), Nd2 LiRuO6 (NLR) and Sm2 LiRuO6 (SLR) crystals are reported. The linear optical properties of these compounds have been investigated using density functional theory calculations. The optical anisotropy in these compounds is revealed from their computed optical properties, such as their complex dielectric functions and refractive indices. The calculations show that SLR has a relatively large birefringence (Δ n = 0.06) compared to NLR and PLR, which is important for mid-infrared nonlinear optical applications. We propose that the O 2p to Ru 4d transition is primarily responsible for the origin of optical activity in these materials while the origin of the optical anisotropy in these materials results from the asymmetrically oriented Ru–O bonds in the RuO6 octahedra of the unit cell. The evolution of the Ru 3d core-level signals as obtained from the X-ray photoemission spectroscopy measurements provide confirmation of a dynamic increment in the electron correlations as we move from PLR and NLR to SLR.